PENGARUH FAKTOR HARGA, KEAMANAN, KENYAMANAN DAN KETEPATAN WAKTU TERHADAP PEMBELIAN TIKET KERETA API EKONOMI AC PENATARAN JURUSAN SURABAYA-MALANG-BLITAR ( Studi Kasus Pada Penumpang Kereta Api Ekonomi Penataran Di Stasiun Kota Baru Malang ) - Eva Ruswinda; Rois Arifin; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
Abstract This research uses a quantitative approach by collecting data through quesioner methods. The population in this study was the ticket buyers of the Penataran train in Surabaya - Malang - Blitar. The sample is 97 respondents with data collection techniques using a questionnaire. The purpose of this study are: 1) to find out the factors of price, security, comfort, and timeliness have a partial effect on the purchase of Railroad train tickets, 2) to find out the factors of price, security, convenience, and timeliness have an effect on purchasing train tickets upgrading fire.The results showed that 1) the factors of price, security, comfort, and timeliness have a simultaneous effect on the purchasing decisions of train tickets, 2) the factors of price, security, convenience and timeliness have a partial effect on the decision to purchase train tickets.Keywords:Price factor, safety factor, comfort factor, timeliness factor, ticket purchase, upgrading train